Chivalry in Medieval Portugal - Aguiar,Miguel (2015)
This article seeks to understand the different stages in the spread and development of chivalric ideals as a feature that marked the identity of the main socio-political groups in medieval Portugal. For this purpose, a diachronic approach is adopted, while, at the same time, a comparison is made with other European areas, especially the Iberian Christian kingdoms. The sources used for the writing of this study ranged from chronicles to genealogical literature, legislative compilations, chivalric treatises and diplomatic documents.